Reflecting on Bodily Listening in Place: An Intercultural and Intersensory Research-Creation Project - Bath, Paula; Girault, Tiphaine; Waterman, Ellen (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article discusses a research-creation process by three interdisciplinary artists who worked across hearing and deaf experience to reorient aurality in musicking through a process of inter-sensorial exploration. For most musicians listening is unquestionably oriented to the sensory regime of aurality. Increasingly, however, this orientation is being challenged through haptic, kinetic, and visual musicking by deaf musicians, and this inspired hearing flutist and vocalist Ellen Waterman to reorient the role of audition in her improvisational practice. In dialogue with multisensory performance artists and critical theorists Paula Bath (hearing) and Tiphaine Girault (deaf), Waterman embarked on a research-creation project to create Bodily Listening in Place, an instructional score for intersensory improvisation. We discuss our iterative and multi-model practice-based research process, which involved the exchange of sonic, haptic, kinetic, linguistic, and graphic media in response to bodies in place. Photographs, sound, and video examples further explain our process. As is well documented in the anthropology of the senses (Howes), sensory perception is constructed and lived differently in different periods and societies, reflecting the diversity through which people perceive and understand their environments. We argue that, through an expanded conception of listening as attentiveness (Hahn; Oliveros), we can move beyond current normative notions of aurality to develop a broader, intersensory awareness and conception of musicking. Such expanded listening affords a means to further establish the links between people, their histories, experiences, senses of place, and environments.